Marxist education and teacher education against capitalism in neoliberal/neoconservative/neofascist/times - Hill, Dave (Cadernos do GPOSSHE On-line, 2019)
In this article I analyse global and national neoliberalisms- economic and social class war from above- neoconservatisms which are leading to and connected with NeoFascisms- with their scapegoating, racism, xenophobia, misogyny, heterophobia, militarism and the attacks on dissent- whether electoral, media, or from academics/ universities and workers’ organisations and actions. Six prime examples are Erdogan in Turkey, Bolsonaro in Brazil, Trump in the USA, Orban in Hungary, the Law and Justice government in Poland, and the racist government in Italy, in effect led by Salvini. Across Europe Far-right anti-immigrant, xenophobic and ultra nationalist authoritarian parties are recruiting and becoming electorally significant- and, in some cases, significant on the streets. Critique social democratic reformist parties and governments for adopting neoliberal austerity policies and thereby becoming delegitimised, together with the too-often `accomodationist’ trade union and party leaderships. and critically examine prospects for left social democracy as represented, for example, by the Jeremy Corbyn led Labour Party in the UK. Much of the article is devoted to the resistant and the revolutionary role of teachers, academics and education/ cultural workers in different arenas, from national and local electoral and direct action politics/ Focusing on Critical Education, Critical Educators, Marxist Education, Marxist Educators, I seek to address four aspects of education: pedagogy, the curriculum, resistance in the classroom and the hidden curriculum, and the structure of schooling nationally and locally (within-school). I conclude by setting out what is specifically Marxist about the proposals set out. These are: (1) Class Analysis: the Capital-Labour Relation; (2) Capitalism must be replaced by Socialism and that change is Revolutionary; and (3) Revolutionary Transformation of Economy and Society needs to be preceded by and accompanied by a Class Programme, Organisation, and Activism. Regarding capitalism, our task is to replace it with democratic Marxism, to lead, firstly, into socialism, and ultimately, into communism. As teachers, as educators, as cultural workers, as educational, union and party activists, as intellectuals, we have a role to play.